KESEPAKATAN KELEMBAGAAN KONTRAK MUDHARABAH DALAM KERANGKA TEORI KEAGENAN - Asfi Manzilati (Jurnal Keuangan dan Perbankan, 2017)
This research aimed to know how the banker (as principals) interact with customers (as agents) in creating andenforcing a contract of mudharabah, offer an alternative arrangement of mudharabah contract resultingmudharabah rules (institutions) that benefited both parties (principal and agent). With in-depth interviews,two important findings were obtained: character of prospective clients was an important determinant of thecreation of a contract as collateral material. It should not be used as a tool to compensate investment risk,monitoring was a key to the process of contract enforcement. Based on the findings and review of relatedliterature, a design of mudharabah rules (institutions) that were expected more fair and beneficial to bothparties namely the bank / shohibul mal as the principal and client or mudharib as an agent could be developed.